Mean Waiting time Analysis on Bukl Arrival Fuzzy Queueing System Using Maximum Likelihood Estimation - et. al., V.Ramalakshmi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Consider the Erlang k-phase queueing system on fuzzy environment and to obtain the optimal value of mean waiting time for the concern system. In this regard, here we proposed new algorithm, using alpha - cut method to construct the different value in the range of uncertain and analyze the system performance level by the MINLP method and discussed a numerical example.